FEMSLASH FANFICTION AND LESBIANISM: EFFORTS TO EMPOWER AND EXPRESS ASIAN AMERICAN WOMAN SEXUALITY - Tyas Willy Kartika; Maria Elfrieda C.S.T (Universitas Gadjah Mada, 2021)
The existence of fan fiction nowadays shows more progressive development especially in this digital era when people does not only use internet for communicating and socializing across time and space but they also show their creativity, one of them is by writing a fan fiction. By writing fan fiction in online platforms, people get the opportunity to express their interests and their identities. This opportunity is also obtained by minority groups such as LGBTQ+ where they can express their identity through fan fiction. LGBTQ+ community utilizes online platform as the tool that brings benefit for them. In this case, writing fan fiction in online platforms allows people to create the preferable representation of minority groups and empower them as the part of LGBTQ+ community. This phenomenon can be seen through a website named Asianfanfics.com which shows an increasing number of fan fictions especially the ones with lesbian related tags such as girl x girl, lesbian, and femslash. Particularly, through the femslash subgenre, people use fan fiction to question the heteronormativity. Regarding to this phenomenon, an interview was conducted by choosing three Asian American fan fiction writers from Asianfanfics.com as the interviewees. Furthermore, by using gender theory and intersectionality, this article focuses on how fan fiction becomes a safe space to express their sexual identities and how lesbian relationship is viewed by Asian families.